2022
DOI: 10.1111/ssqu.13220
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Preferences for Comprehensive Electoral Reform in the United States

Abstract: The aim of this study is to examine whether Americans have a latent attitude toward comprehensive electoral reform the determinants of this attitude. Methods: The article creates and validates an index of election reform attitudes; examines the independent and interactive roles of partisanship, political interest, electoral fortunes, and satisfaction with democracy on these attitudes. Results: While a majority of Americans favor comprehensive election reform, this desire is strongest among Democrats, independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…These replicated questions were used in previous research as a means of validating the representativeness of the survey sample (Coll et al. 2022). The 2023 survey reported similar levels of support as the earlier 2022 survey, showing that the validation worked.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These replicated questions were used in previous research as a means of validating the representativeness of the survey sample (Coll et al. 2022). The 2023 survey reported similar levels of support as the earlier 2022 survey, showing that the validation worked.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Other studies find roughly two‐thirds of Americans desire a wide range of reforms to U.S. elections and that support varies predictably by partisanship, satisfaction with democracy, and feelings of often losing in politics (Coll, Tolbert, and Ritter 2022; see Bowler and Donovan 2018 on convenience voting reform).…”
Section: Public Opinion About Primary Elections and Election Reformmentioning
confidence: 99%
“…Third, it is reasonable to presume that evaluations of democracy mirror the preferences of political "winners" and "losers" such that supporters of the party that controls state government will evaluate state democratic performance more favorably than supporters of the minority party in the state. This "winnerloser gap" has been examined in previous research at the national level where scholars have identified that voters who support the winning side report higher levels of efficacy, are more trusting, and are more satisfied with democracy (Coll et al 2022;Bowler and Donovan 2002;Anderson et al 2005;Craig et al 2006;Norris 2019). Voters are also increasingly willing to look the other way and disregard their stated support for democracy if their own political party is in power (Simonovits, McCoy, and Littvay 2021) and are prone to follow the cues and rhetoric they receive from elites even further undermining democratic norms (Clayton et al 2021).…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…This “winner–loser gap” has been examined in previous research at the national level where scholars have identified that voters who support the winning side report higher levels of efficacy, are more trusting, and are more satisfied with democracy (Coll et al. 2022; Bowler and Donovan 2002; Anderson et al. 2005; Craig et al.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…Public opinion on voter ID laws is more complicated than one might expect. While support for voter ID requirements is highly correlated with belief in widespread fraud (Wilson & Brewer, 2013), public support for these requirements is also very high broadly, with majority support across all parties, races, and other major identity groups (Coll et al, 2022b), although the highest levels of support do come from Republicans/conservatives (Rocha & Matsubayashi, 2014; Wilson & Brewer, 2013). This broad-based support is surprising given research suggesting these laws tend to have a suppressive effect on eligible voters generally and Black voters specifically (Barreto et al, 2019; Hajnal et al, 2018; Hajnal et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%